Suicidality Risk Factors Across the CARE-HD, 2CARE, and CREST-E Clinical Trials in Huntington Disease. Issue 2 (April 2022) - McGarry, Andrew; Auinger, Peggy; Kieburtz, Karl D.; Bredlau, Amy-Lee; Hersch, Steven M.; Rosas, H. Diana
Abstract : Background and Objectives: Suicidality is a common concern in the routine care of persons with Huntington disease (HD) and for the many participants in HD clinical trials. In a previous analysis, we identified baseline and time-dependent factors associated with suicidal ideation and attempts from 2CARE, a large, randomized, double-blind clinical trial. Methods: The present analysis extends our prior methodology to 2 other large interventional HD clinical trials, CARE-HD and CREST-E. Results: We observed relationships across studies between suicidality events and prior suicidal ideation at baseline, antidepressant/anxiolytic use, chorea, increasing age, and several domains in the Unified Huntington Disease Rating Scale (UHDRS) Behavioral Assessment (depressed mood, low self-esteem, aggression, and active suicidality). Discussion: These data may form the basis for a subscale of demographic and UHDRS items with the potential for prospectively identifying suicidality risk in HD clinics and clinical trials. Trial Registration Information: 2CARE and CREST are registered at clinicaltrials.gov . 2CARE NCT00608881, registered February 6, 2008; first enrollment March 2008. CREST-E NCT00712426, registered July 10, 2008; first enrollment September 2009. CARE-HD, not registered; first enrollment July 1997.